THE POWER OF MULTIMEDIA TO ENHANCE LEARNERS’ LANGUAGE SKILLSIN MULTILINGUAL CLASS - Zaim Zaim (Proceedings of ISELT FBS Universitas Negeri Padang, 2016)
The aim of language teaching is to enable learners to be fluency in the language being learned. Some efforts have been done by the teachers in the process of teaching and learning in language class such as using various methods and strategy of teaching to make the students learn in the class but the results are still far from the expectation. Multimedia, that can be found easily nowadays, can be used to enhance the learners’ language skills. The use of silent story, picture cued, TV news, comic strips are among the multimedia that can be used by teachers as the solution to make the learning process more motivated for the learners to practice their language skills orally and in written form. Multimedia has a power to motivate learners practice their language in a contextual situation then they acquire the language.